PENDAYAGUNAAN ZAKAT PRODUKTIF; Studi Analisis di Badan Amil Zakat Nasional Kabupaten Jepara - Imron Choeri (Faculty of Sharia and Law UNISNU Jepara, 2016)
This article aims to discuss how the source, the use, and the management of the Zakat funds by the National Zakat Board of Jepara Regency? The results showed that in zakat management by the National Zakat Board of Jepara in outline has been carried out in accordance with the provisions of Islamic law, both in fundraising, management and distribution. First, the county charity fund source Jepara obtained through cooperation with the government, in cooperation with UPZ districts, proactive by officers, as well as independently conducted by muzakki to deliver the funds to the charity BAZNAS Jepara district office or transfers through accounts that have been provided. One of the success factors in the acquisition of the source of funding is through the role of regent of Jepara Jepara Regent circular requiring all employees issued zakat by cutting salaries through the treasurer. Second, management of zakat funds already done optimally performed by BAZNAS Jepara regency good for consumptive activities and productive. Third, the utilization of Zakat funds is not maximized for productive activities that do not have an impact on poverty alleviation efforts in the district of Jepara. Keywords: Islamic Law, Zakat Productive, Poverty Alleviation